King Of The Wind - Henry, Marguerite; Dennis, Wesley (New York Aladdin Books, 1991)
Sham and the stable boy Agba travel from Morocco to France to England where, at last, Sham's majesty is recognized and he becomes the "Godolphin Arabian," ancestor of the most superior Thoroughbred horses
American corner
The Story of the Godolphin Arabian
John Newbery Medal
11
Keywords: Arabian horse -- Fiction; English Fiction; English stories